Impact of Metabolic Surgery on Type 2 Diabetes Mellitus, Cardiovascular Risk Factors, and Mortality: A Review - Cohen, Ricardo; Sforza, Noelia S.; Clemente, Romina G. (Current Hypertension Reviews, 2021)
Background: The association between obesity and a reduction in life expectancy is well established, and cardiovascular disease is a leading cause of mortality. Bariatric surgery has long been established as the most effective and durable intervention for obesity, and is the only intervention for obesity that consistently improves multiple comorbidities, reduces cardiovascular disease and long-term mortality. The purpose of this review is to describe the impact of metabolic/bariatric surgery on type 2 diabetes mellitus and cardiometabolic parameters, including cardiovascular mortality. Methods: A systematic literature search of Pubmed, MEDLINE, and Cochrane Central Register was performed. We included randomized controlled trials, meta-analysis, case-control trials, and cohort studies that contain data on reductions in cardiovascular risk factors and cardiovascular mortality in subjects who underwent metabolic/bariatric surgery from January 1, 2005 to June 1, 2020. Conclusion: There is sufficient evidence from randomized controlled trials that metabolic/bariatric surgery is associated with a significant improvement of all cardiovascular risk factors. Although studies are showing a reduction of macrovascular events and cardiovascular mortality, these findings come from observational studies and should be confirmed in randomized clinical trials.
Keywords: cardiovascular mortality